"Until I know this sure uncertainty": actor training and original practices. Issue 1 (2nd January 2021) - Hay, Chris; Dixon, Robin
Abstract : In April 2017 we worked with a small group of trained actors at the University of Sydney on a project examining emotion and spatial dramaturgy in Shakespeare's The Comedy of Errors . Where possible, elements of original practices were applied in rehearsals for this project; in particular, working in 'parts' and without a central directorial figure exercising creative authority over the process. Strikingly, otherwise confident actors with considerable expertise in Early Modern and contemporary performance practices expressed a range of anxieties about these rehearsal techniques, admitting that they were challenged by these methods of working in ways that went beyond the merely practical. This paper examines the benefits and implications of employing historically-informed rehearsal methods when working with Shakespearean drama in twenty-first century training contexts. Although attempts to slavishly follow original practices may be of limited utility, plays of the period were written within an ecology of practice that has left subtle and overt traces in the texts. Establishing a baseline of conventional practice and providing actors with a 'toolkit' of memorisation, characterisation and physical techniques may prompt fluent performance of these plays — but also poses challenges that reveal the implicit biases and blind spots of contemporary actor training. In this paper, we ask how historically-informed modes of rehearsal and performance practice might be made compatible with contemporary actor training.